MOTIVASI PNS (PEGAWAI NEGERI SIPIL) MEMBUKA USAHA - Hendra, Khairani Putri; Yanladila Yeltas Putra (CV. Causalita Dynamic Solutions, 2024)
The large number of people who are entrepreneurs in a country is one of the biggest factors in the advancement of a country. Including one of them civil servants who already have a permanent job they also have their own business due to the motivation to open a business. Motivation to open a business is an impulse that is influenced by oneself (internal) or outside oneself (external) that moves individuals to behave, act, and think consciously to open a business or become an entrepreneur. This study aims to determine, describe and explain the motivation to open a business in civil servants, by conducting semi-structured interviews with two research subjects, namely one woman and one man who work as civil servants and have had a business for more than five years. This research was conducted using qualitative research methods with a phenomenological approach. Data analysis in this study used data analysis techniques according to Miles and Huberman which consisted of three steps, namely: data reduction, data presentation, and data verification. The results of the study obtained that the research subjects opened a business influenced by internal factors such as self-will, hobbies, skills, desire to be independent, ambition, and desire to help. Then it is also influenced by external factors such as family, work environment, and family economy. The difference between the two research subjects is that the female subject opened a business because of the desire to be independent while the male subject opened a business because he wanted to make his business an icon in the area where he lived. In addition, the similarities between the two research subjects are that they see, find and take advantage of business opportunities when working as civil servants. Another similarity is due to running two professions, namely as a civil servant and entrepreneurship, both subjects have time management and the role of family in the business they run.